2020
DOI: 10.2147/ijn.s236897
|View full text |Cite
|
Sign up to set email alerts
|

<p>Two-Photon Photoexcited Photodynamic Therapy with Water-Soluble Fullerenol Serving as the Highly Effective Two-Photon Photosensitizer Against Multidrug-Resistant Bacteria</p>

Abstract: Background: Multidrug-resistant (MDR) bacterial strain is a serious medical problem. Methicillin-resistant Staphylococcus aureus (MRSA) is resistant to many antibiotics and is often associated with several diseases such as arthritis, osteomyelitis, and endocarditis. The development of an alternative treatment for eliminating MDR bacteria such as MRSA has attracted a considerable amount of research attention. Moreover, the development of a material for highly efficient generation of reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, when suspended in tetrahydrofuran, fullerenols exhibited no photoactivity. Kuo et al (2020) reported massive production of ROS and complete elimination of methicillin-resistant S. aureus by water-soluble fullerenol C 60 (OH) 30 under two-photon excitation in the near-infrared region (760 nm).…”
Section: Application Of Fullerene Derivatives In Antimicrobial Photod...mentioning
confidence: 99%
“…However, when suspended in tetrahydrofuran, fullerenols exhibited no photoactivity. Kuo et al (2020) reported massive production of ROS and complete elimination of methicillin-resistant S. aureus by water-soluble fullerenol C 60 (OH) 30 under two-photon excitation in the near-infrared region (760 nm).…”
Section: Application Of Fullerene Derivatives In Antimicrobial Photod...mentioning
confidence: 99%
“…As shown in Figure 1 a, the fullerenols are circular-like particles with average diameters of 1.8 nm and well dispersed without aggregation. The lattice distance (0.213 nm) corresponding to d-spacing of fullerenol lattice fringes is clearly observed in high-resolution TEM (HRTEM) images ( Figure 1 a) [ 29 , 30 ]. The similar sphere-shaped morphology of NDs with average diameters of 6.8 nm is shown in Figure 1 b.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to chemodynamic therapy, photodynamic therapy (PDT) nanomaterials have been widely used in diagnosing and treating tumors, but relevant studies have assessed the antibacterial effect of PDT. Kuo et al [ 59 ] performed water-soluble C60 (OH) 30 on Gram-positive MRSA to prove that nanomaterial photochemokinetics also effectuate sterilization. In this study, ROS were produced using water-soluble fullerenol, and PDT killed most Gram-positive bacteria within a short period.…”
Section: Nanomaterials For Diagnosis and Treatment Of Osteomyelitismentioning
confidence: 99%